The Influence of Perceived of Usefulness, Ease, Risk and Trust on Continuous Intention in Using BRI Mobile Banking (Study of BRI Mobile Banking Users in Banyumas Regency) - Kirani, Nabila Sasi; Widyaningtyas, Dian; Handayani, Erna; Randikaparsa, Irawan (Asian Journal of Management Analytics, 2025)
This study attempts to investigate the influence of perceptions of usefulness, convenience, risk and trust on continuous intention in utilizing BRI m-banking. This research was conducted on BRI mobile banking users in Banyumas Regency as research objects. The variables included in this study are those of benefit, convenience, risk and trust as independent variables, while continuous intention is the dependent variable. This study's methodology is quantitative. The sample that was utilized in this research was 130 respondents obtained through the purposive sampling method. Questionnaires with a Likert scale were distributed as part of this data collection method. The data obtained was processed utilizing SPSS version 26.